2009
DOI: 10.1590/s1679-62252009000100008
|View full text |Cite
|
Sign up to set email alerts
|

Iheringichthys labrosus (Siluriformes: Pimelodidae) in the Piquiri River, Paraná, Brazil: population structure and some aspects of its reproductive biology

Abstract: The purpose of this study was to analyze the population structure (spatial and temporal distribution, sex ratio, length distribution and length/weight relationship) and reproductive biology of Iheringichthys labrosus. This species is of importance as fisheries resource in the Paraná River basin. Fish were sampled, bimonthly, with gill and trammel nets at three sampling sites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
6
13
1
Order By: Relevance
“…The weight-length relationship differed from that reported previously by Teixeira-de Mello et al (2008) in Uruguay River, and from Holzbach et al (2009) in Piquiri River. Both studies indicated a positive allometric growth for this species.…”
Section: Morphometric Relationshipscontrasting
confidence: 98%
“…The weight-length relationship differed from that reported previously by Teixeira-de Mello et al (2008) in Uruguay River, and from Holzbach et al (2009) in Piquiri River. Both studies indicated a positive allometric growth for this species.…”
Section: Morphometric Relationshipscontrasting
confidence: 98%
“…The explanation for a higher condition factor in males in the period preceding the breeding season can be explained by a greater accumulation of reserves during that period for use in the maturation period, when such reserves are spent. This is behavior also observed in other species (Agostinho et al, 1990;Freitas et al, 2011;Holzbach et al, 2009). In females, the total condition factor (K) is greater in October/November, probably as a result of a greater influence of gonad weight during this period, as it is the peak period of gonadal maturity.…”
Section: Discussionsupporting
confidence: 84%
“…Variation in this index over the year can be used as additional data in the study of seasonal cycles of feeding and reproduction (Braga, 1986;Lima-Junior et al, 2002.) The condition factor and gonadosomatic indexes, which reflect the development of ovaries or testicles as percentages of total weight, can indicate the breeding season of a given species, and they are being frequently used for this purpose by many researchers in several Brazilian basins (Vazzoler, 1996;Costa et al, 2005;Ribeiro et al, 2007;Holzbach et al, 2009). Both males and females showed greater differences between K and K´ from August/September through February/March.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work analyzing the reproduction period of this species in Brazil had shown a peak of maturity from October to January. 35,36 If this is also the case for I. labrosus of lower Río Uruguay, the sampling scheme of this work would correspond with the beginning and the end of the spawning season of this species. The clear reduction in the gonadal size between November 2009 and April 2010 is also in line with this idea (see Table 3).…”
Section: Discussionmentioning
confidence: 99%